2019
DOI: 10.17759/autdd.2019170203
|View full text |Cite
|
Sign up to set email alerts
|

Model of Imposed Adaptation in Childhood Learning Environments — Application to Autism. A precarious game of developmental Jenga

Abstract: Academic and social expectations place ever-increasing stressors on young children. The failings of our academic system to address these concerns greatly impact the general population but may be even more harmful for children on the autism spectrum, who are shown to have significantly higher rates of anxiety, depression, and suicide in later life. The relational and ecological demands indiscriminately placed on autistic children to achieve one-size-fits-all academic learning goals is examined in this paper, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Spielmann and Porter found that children with autism often exhibit a range of low-motivation behaviors such as tantrums, disobedience, and inattention and attempts to escape the teaching environment [ 6 ]. Cahill et al also found that lack of motivation is a common problem for children with autism and is what makes children with autism deficient in play and social interaction [ 7 ].…”
Section: Related Workmentioning
confidence: 99%
“…Spielmann and Porter found that children with autism often exhibit a range of low-motivation behaviors such as tantrums, disobedience, and inattention and attempts to escape the teaching environment [ 6 ]. Cahill et al also found that lack of motivation is a common problem for children with autism and is what makes children with autism deficient in play and social interaction [ 7 ].…”
Section: Related Workmentioning
confidence: 99%
“…His research used a scientific method and the results are accurate, but it is slightly lacking in practicality due to the complexity of the operation. [9] studied relational and ecological demands on children with autism, as well as exploring current evidence on the risks faced by adolescents with autism. His research opened up more possibilities for the application of sensory integration.…”
Section: Related Workmentioning
confidence: 99%